Insulin-Like Growth Factor I Receptor Signaling Is Required for Exercise-Induced Cardiac Hypertrophy - Kim, Jaetaek (The Endocrine Society, 2008)
The receptors for IGF-I (IGF-IR) and insulin (IR) have been implicated in physiological cardiac growth, but it is unknown whether IGF-IR or IR signaling are critically required. We generated mice with cardiomyocyte-specific knockout of IGF-IR (CIGF1RKO) and compared them with cardiomyocyte-specific insulin receptor knockout (CIRKO) mice in response to 5 wk exercise swim training. Cardiac development was normal in CIGF1RKO mice, but the hypertrophic response to exercise was prevented. In contrast, despite reduced baseline heart size, the hypertrophic response of CIRKO hearts to exercise was preserved. Exercise increased IGF-IR content in control and CIRKO hearts. Akt phosphorylation increased in exercise-trained control and CIRKO hearts and, surprisingly, in CIGF1RKO hearts as well. In exercise-trained control and CIRKO mice, expression of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) and glycogen content were both increased but were unchanged in trained CIGF1RKO mice. Activation of AMP-activated protein kinase (AMPK) and its downstream target eukaryotic elongation factor-2 was increased in exercise-trained CIGF1RKO but not in CIRKO or control hearts. In cultured neonatal rat cardiomyocytes, activation of AMPK with 5-aminoimidazole-4-carboxamide-1-β-d-ribofuranoside (AICAR) prevented IGF-I/insulin-induced cardiomyocyte hypertrophy. These studies identify an essential role for IGF-IR in mediating physiological cardiomyocyte hypertrophy. IGF-IR deficiency promotes energetic stress in response to exercise, thereby activating AMPK, which leads to phosphorylation of eukaryotic elongation factor-2. These signaling events antagonize Akt signaling, which although necessary for mediating physiological cardiac hypertrophy, is insufficient to promote cardiac hypertrophy in the absence of myocardial IGF-I signaling.